Achievements of Skill Development in Making India a Skill Capital 2015-16: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
When the government announced its skill development training totals for 2014-2015 last month, critics were quick to condemn the Skills Ministry and government departments that fell short of the training goals.